The Importance of National Integration to Strengthen Religious Diversity in Community Life - Nur Azlin Putri; Woolnough Cale; Mahon Nitin (Yayasan Adra Karima Hubbi, 2023)
Background. Indonesia is the 4th most populous country after the United States, recorded more than 267 million people in SUPAS 2019, which consists of a variety of social diversity, religions, ethnic groups, cultures. Purpose. This research uses a literature approach that collects literature that has a relationship with the research conducted. Method. There are several factors that influence the diversity of Indonesian society, both from within and outside the community itself. This diversity is a challenge that can be a threat to the integrity of the Indonesian nation. This research aims to analyze diversity. Results. he results of this study show that in a diversity, efforts are needed to improve harmony between tribes, religious communities and other social groups which can be done through cooperation using the principles of togetherness, equality and mutual respect as the national integration of the Indonesian nation. Conclusion. The muraja'ah method carried out in the tahfiz house is quite good, because the teacher teaches muraja'ah by applying it before each study or ziyadah together, namely by doing a relay which will make it easier for tahfiz students to repeat their memorization.